Isolation and Identification Cellulolytic Bacteria from Termite Gut Obtained from Indralaya Peatland area. Issue 1 (November 2021) - Oktiarni, D; Hermansyah,; Hasanudin,; Miksusanti,; Nofyan, E; Kasmiarti, G
Abstract: The production of second-generation bioethanol as renewable energy has developed very rapidly and has become a promising alternative energy source. Bioethanol production using biomass can be obtained alternatively from cellulose in wood, sawdust, organic waste, and agricultural waste. This research used termites obtained from Indralaya peatland area as organisms that can decompose cellulose into glucose with the cellulase enzymes produced by bacteria in their digestive tract. Cellulases are enzymes capable of hydrolyzing lignocellulose into glucose. The study aimed to isolate and identify of cellulolytic bacteria from termite gut obtained from Indralaya peatland area. The bacterial isolates were classified by using morphological and biochemical standard methods, and identification based on Bergey's Manual of Determinative Bacteriology. Cellulolytic bacteria of termite gut were isolated and cultured on CMC (Carboxymethyl cellulose) agar medium. The activity of cellulolytic bacterial was conducted based on halo area and cellulolytic index on CMC agar medium. Among 64 isolates of bacteria, 24 isolates were identified as cellulolytic bacteria. Futhermore, our isolates with higher cellulolytic index were identified as the Staphylococcus, Microbacterium, Bacillus, and Brevibacterium genus.